Membumikan Al-Quran Melalui Penerjemahan dan Pendistribusian Mushaf Al-Qur’an Juz 30 Terjemah Bahasa Bali di Kampung Muslim di Klungkung - Ramdhani, Fajri Zulia; Iswahyuni (Proceedings of Annual Conference on Community Engagement, 2022)
Generally, Muslims have not been able to understand the Qur’an through Arabic directly. The translation of the Qur’an is one of the methods used to interpret the verses of the Qur’an. However, the translation of the Qur’an in the context of Indonesianness only in Indonesian is considered insufficient. This is because some Muslim communities do not use Indonesian, but regional languages as their daily language. STAI Denpasar Bali conducted a review and published mushaf Al-Qur’an Juz 30 Balinese Translation. The mushaf was reviewed and distributed, one of which was in the Muslim Village in Klungkung. This devotion aims to ground the Qur’an through the local language, especially to facilitate students’ access to Islamic literature in the midst of an economic crisis due to pandemic conditions. The method in implementing this service is based on Participatory Action Research. This service activity resulted in a review of the results of the Balinese Translation Mushaf which was then distributed and utilized by the community and students in the Muslim Village in Klungkung.